Resources: Agriculture, nutrition, and health - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent publications and websites examine the critical links between agriculture, nutrition, and health.